Penerapan Digital Marketing Terhadap peningkatan Amal Usaha Muhammadiyah di Ranting Muhammadiyah Cabang Medan Denai - Linzzy Pratami Putri; Irma Christiana; Ichwan Arsy Muharmansyah; Aflahun Fadhly Siregar (CERED Indonesia Publishing, 2025)
This community service activity was carried out to increase promotion and public awareness about the existence of the Muhammadiyah Medan Denai Branch charity, with a focus on the use of digital technology to achieve this goal. Socialization and discussion methods are used to provide understanding to administrators and teachers at Muhammadiyah charities about the importance of digital marketing. The results include registering the location of the Medan Denai Branch of Muhammadiyah Branch on Google Maps and promotion via social media. Supporting factors include positive responses from administrators and teachers as well as stable internet access, while obstacles include limited time and communication. In conclusion, implementing digital marketing in Muhammadiyah's charitable efforts is a relevant and important step to expand reach, increase promotional effectiveness, and strengthen communication with stakeholders.